Management of the axilla after neoadjuvant chemotherapy: Can axillary needle biopsy replace sentinel node biopsy? - Yıldırım, Emine; Basım, Pelin; Uçar, Neşe; Bektaş, Sibel; İşcen, Kutay; Karcı, Ebru; Özdemir, Asena Ayça (My University, 2024)
Background/Aim: The aim of the study was to investigate whether it is possible to evaluate the axilla after treatment without performing sentinel lymph node biopsy (SLNB) in breast cancer patients with biopsy-proven axillary lymph node metastases who received neoadjuvant chemotherapy (NAC). Patients and Methods: This prospective, randomized, clinically designed study included patients with clinical T1-3 and biopsy-proven N1 breast cancer. Prior to the surgery scheduled after NAC, the patients were randomized into two groups. A biopsy sample was obtained from the clipped axillary lymph node, which was preoperatively known to be metastatic, using fine needle aspiration (FNAB) in the first group and core needle biopsy (CNB) in the second group. The predictive ability of the two biopsy methods for the SLNB results was evaluated. Results: The study included 50 female patients with breast cancer, with a mean age of 48.4±10.72 years. In both groups, metastasis was detected in nine patients, and no metastasis was seen in 14 patients. In intergroup comparisons, all patients with metastasis in the FNAB group also had metastasis according to SLNB, while 21.4% of the cases without metastasis in this group were metastatic according to SLNB. In the CNB group, metastasis was observed in all patients with metastasis according to SLNB, while no metastasis was detected in those who were reported to have no metastasis by SLNB. The accuracy, specificity, and sensitivity values for the prediction of SLNB results were all found to be 100% for CNB, whereas they were 87%, 100%, and 75%, respectively, for FNAB. Conclusion: Both CNB and FNAB could potentially replace SLNB due to their high accuracy rates in evaluating the axilla after NAC. The sensitivity and accuracy of CNB were determined to be higher.
Keywords: Axillary Lymph Node Dissection; Axillary Management; Breast Cancer; Neoadjuvant Chemotherapy; Sentinel Lymph Node Biopsy